Sovereign indebtedness and financial and fiscal conditions - Afonso, António (2022)
We empirically assess the magnitudes of sovereign indebtedness responses for a sample of 123 Advanced and Emerging Market Economies, between 1980 and 2018, taking into account the changing characteristics of financial markets, notably the Global and Financial Crisis. Our results show that when the financial conditions are more stressful, for instance, higher yield spreads or a heightened degree of financial stress, fiscal authorities use more actively their primary balance to reduce sovereign indebtedness, which is not the case when financial market conditions are more benign. This is notably true for the case of Emerging Market Economies sovereigns, who most likely then struggle more to fund themselves.